The Effectiveness of Movie as a Media in Increasing Vocabulary Learning at SMA N 9 Jambi City - Wennyta Wennyta (Universitas Batanghari Jambi, 2023)
This research aims at determining the effectiveness of using movie in increasing students’ vocabulary masteryof grade 11th at SMA N 9 Jambi city. This research was conducted with two classes of samples. Class samples were taken by using random sampling technique. Classes were first drawn as the experimental class A and second drawn was labeled as control class (class B). From the hypotheses, it is expected that using a movie is very effective in increasing students vocabulary when they learn English compared with those who do not use movie as a media in learning vocabulary. From the results of the hypothesis test it is obtained that tcount 1,76 > t table 1,67. From the analysis that has been conducted on the pre-test and post-test, it can be concluded thatH0 is rejected so it can be concluded in accordance with the hypothesis that English vocabulary learning outcomes of students who use movie as a media is more effective rather than the English vocabulary learning outcomes of students who do not use of it